(untitled) (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-122-130 Spiritual prose based on the principle of theocentrism and addressing the Orthodox worldview is an actual phenomenon in the modern Russian literature. In many works related to this phenomenon, the main place is occupied by an evolving character who goes through a difficult path of spiritual rebirth. The action of E.G. Vodolazkin’s novel “The Laurel” takes place in the Middle Ages and tells about the life and spiritual evolution of a doctor who eventually acquires the features of a righteous hero. The traditions of spiritual prose are embodied through the level of nominations: the hero has four names (Arseny, Ustin, Ambrose, Laurus), which symbolize the four stages of a person’s life who embarked on the path of monastic service. The key value vectors reflected in the work are love, mercy, forgiveness, compassion and sacrifice. The hero himself experiences suffering and strives to help others free themselves from internal conflicts, that allows him to get closer to God. In addition, the author refers to church sacraments and rituals, such as baptism and monastic tonsure, which also indicates the reflection of the traditions of spiritual prose in the novel. Key words: spiritual prose, novel “Laurel”, life, evolving character